2010
DOI: 10.1007/s11104-010-0589-6
|View full text |Cite
|
Sign up to set email alerts
|

Lead bioaccumulation in Acacia farnesiana and its effect on lipid peroxidation and glutathione production

Abstract: Phytoremediation offers a cheap, efficient and environmentally friendly option for cleaning sites contaminated with toxic elements. However, there is a need to find new plant species for phytoremediation and to understand the mechanisms involved in processes such as tolerance, accumulation, exclusion and metabolism of toxic metals in plants. Thereby, in this study, the ability of Acacia farnesiana (L.) Willd to tolerate and accumulate lead was analyzed. Seedlings grown in vitro with 250 and 500 mg Pb 2+ L −1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 44 publications
2
13
0
19
Order By: Relevance
“…Increasing concentration of Fe (40, 80, and 160 mM) enhanced lipid peroxidation in Bacopa monnieri (Sinha and Basant 2009). Similarly, elevation in lipid peroxidation in a number of plants due to their exposure to Cu (Posmyk et al 2009;Opdenakker et al 2012;Singh et al 2012;Thounaojam et al 2012;Elleuch et al 2013;Ansari et al 2013a), Ni (Kazemi et al 2010;Gajewska et al 2012), Se (Malik et al 2012), As (Ansari et al 2013b), Pb (Qureshi et al 2007;Maldonado-Magaña et al 2011), Cr (Diwan et al 2008;2010), and some other heavy metals/metalloids was reported to be dependent on their doses and plant types (Sytar et al 2013). The main site of attack by any redox active metal in a plant cell is usually the cell membrane.…”
Section: Metals/metalloidsmentioning
confidence: 96%
“…Increasing concentration of Fe (40, 80, and 160 mM) enhanced lipid peroxidation in Bacopa monnieri (Sinha and Basant 2009). Similarly, elevation in lipid peroxidation in a number of plants due to their exposure to Cu (Posmyk et al 2009;Opdenakker et al 2012;Singh et al 2012;Thounaojam et al 2012;Elleuch et al 2013;Ansari et al 2013a), Ni (Kazemi et al 2010;Gajewska et al 2012), Se (Malik et al 2012), As (Ansari et al 2013b), Pb (Qureshi et al 2007;Maldonado-Magaña et al 2011), Cr (Diwan et al 2008;2010), and some other heavy metals/metalloids was reported to be dependent on their doses and plant types (Sytar et al 2013). The main site of attack by any redox active metal in a plant cell is usually the cell membrane.…”
Section: Metals/metalloidsmentioning
confidence: 96%
“…TF is formulated by comparison between the accumulation of Pb of leaf and stem with root. If TF score > 1 gave indication that vegetation has high ability to absorb and translocate Pb contaminant (Maldonado-Magaña, 2011;Ahmadpour et al, 2012;Arifin et al, 2012;Branzini and Zubillaga, 2013;Madejon et al,2006;Ang et al,2010;Ashraf et al,2011;Madjid et al,2011;Maldonado-Magna, 2011). The accumulation of Pb in mangrove vegetation's also showed the positive correlation between the tolerance of mangrove vegetation with capacity to reduce impact of Pb pollution with precipitation, membrane filtration, electrolyte or liquid extraction, electro dialysis and reversed osmosis activity (Oo, et al, 2009).…”
Section: Bioaccumulation Factor and Translocation Factor Of Pbmentioning
confidence: 99%
“…Informasi tersebut merupakan hal yang paling penting dan strategis dalam rangka mendukung keberhasilan fitoremediasi melalui pengkayaan referensi jenis toleran dan mampu mengakumulasi Pb. Suatu studi menemukan bahwa semai Acacia farnesiana memiliki toleransi dan kemampuan hidup yang baik terhadap Pb hingga konsentrasi 500 mg/L (Magaña et al, 2010 …”
Section: Pendahuluanunclassified
“…IT semai samama menurun pada penambahan Pb hingga konsentrasi 900 mg Pb/kg tailing, dimana IT mencapai nilai 170%. Magaña et al (2010) menemukan bahwa Acacia farnesiana memiliki IT yang sangat tinggi, yaitu > 100% pada pemaparan Pb sebesar 250 -500 mg/L, lalu mengalami penurunan menjadi < 75% ketika paparan Pb berada pada konsentrasi 750 mg/L.…”
Section: Indeks Toleransi Semai Samamaunclassified